56. Ultrasound (US) features of Charcot-Marie-Tooth disease type 1 (HMSN TYPE I). Issue 12 (December 2017) - Sartucci, F.; Bocci, T.; Di Rollo, A.; Del Gamba, C.; Bartolotta, M.; Barloscio, D.; Parenti, L.; Santin, M.
Abstract : Hereditary Motor and Sensory Neuropathies (HMSN) often present a set of challenges on the electrophysiological diagnosis. Even if genetic tests are now available for most of the subtypes, electromyography (EMG) still plays an irreplaceable role in diagnosis. Despite classic division into demyelinating and axonal, many forms of Charcot-Marie-Tooth (CMT) are not easy to diagnose, and ultrasound (US) can make this distinction a bit easier. The presence of an underlying neuropathy can complicate diagnosis of overlapping entrapment syndromes. We investigated 8 patients with HMSN type I (CMT Type I) (5 M and 3 F, mean age 51 ± 8 aa). As control values, we used those of our laboratory, obtained in healthy volunteers, matched for age and sex with patients. We used Telemed Echo-wave II or Esaote MyLab Gamma device; in particular, it was rated cross section area (CSA) observing the main nerve trunks on their entire evaluable length. The average size of nerve was increased in upper limbs and changes were diffuse, while in entrapment neuropathy were focal; also, vague nerve was increased. Moreover, US of nerve trunks provide insight on neuropathy type. Though the literature data concerning US are still limited, is therefore desirable, in the future, a US routine use as a screening tool to help EMG, genetic testing and evaluation of overlapping entrapment syndromes in cases of suspected hereditary neuropathies.